How does knowledge about the criteria for an upcoming test relate to adolescents' situational motivation in physical education? A self-determination theory approach. (November 2019) - Haerens, Leen; Krijgsman, Christa; Mouratidis, Athanasios; Borghouts, Lars; Cardon, Greet; Aelterman, Nathalie
Students' knowledge about the criteria for an upcoming test is a crucial component of assessment quality. Grounded in self-determination theory, we investigated whether knowledge about the criteria for an upcoming test related to students' situational motivation and experienced anxiety during physical education (PE). We also examined whether these relations were: (a) mediated by need-based experiences; and (b) moderated by teachers' motivating style. Participants were 659 students (55.54% boys, 44.46% girls, mean age 14.72 years, standard deviation = 0.94) out of 40 classes from 32 schools taught by 39 different PE teachers. Analyses through multilevel structural equation modeling showed that students with more knowledge about the criteria for an upcoming test valued and enjoyed the lesson more (i.e. autonomous motivation), and felt less aloof (i.e. amotivation). Relations between knowledge about the criteria and students' situational motivation were mediated by experienced need satisfaction. Specifically, students who had more knowledge about the criteria for an upcoming test felt more in charge of their learning process (i.e. autonomy satisfaction), felt more effective in reaching their goals (i.e. competence satisfaction) and felt more connected to the teacher (i.e. relatedness satisfaction). Although relations between knowledge about the criteria and students' motivation were not moderated by teachers' motivating style, teachers' motivating style displayed independent relations with students' motivation. Implications for assessment quality and students' motivation in PE are discussed.